Internal and external motivational factors and their influence on faculty performance at the Pontifica Universidad Católica del Ecuador - Cabezas Guerra, Christian (2012)
This exploratory study analyzed ten factors related to motivation towards job satisfaction, as proposed by Herzberg, Mausner, and Snyderman (1959), and their influence on faculty performance in a representative sample of faculty members of the Pontifical Catholic University of Ecuador between 2010 and 2011. These factors included work characteristics (internal factors) as well as context characteristics where work is performed (external factors). The effect that some faculty members' characteristics, such as faculty time category (i.e. full-time, half-time, part-time), position category, and gender had on job satisfaction and on the motivational factors was also analyzed. Statistical analysis showed that the external factor “job supervision” was a significant predictor of faculty performance. Statistically significant differences were found in some specific motivational factors, depending on the faculty time and position categories. Another statistically significant difference was discovered in the factor “work itself” depending on the faculty gender. Female faculty members showed a higher level of satisfaction in the work itself category than male faculty members.